Exercise therapy, manual therapy, or both, for osteoarthritis of the hip or knee: a factorial randomised controlled trial protocol - Baxter G David; McKenzie Joanne E; Robertson M Clare; Abbott J Haxby; Theis Jean-Claude; Campbell A John (Trials, 2009)
Abstract Background Non-pharmacological, non-surgical interventions are recommended as the first line of treatment for osteoarthritis (OA) of the hip and knee. There is evidence that exercise therapy is effective for reducing pain and improving function in patients with knee OA, some evidence that exercise therapy is effective for hip OA, and early indications that manual therapy may be efficacious for hip and knee OA. There is little evidence as to which approach is more effective, if benefits endure, or if providing these therapies is cost-effective for the management of this disorder. The MOA Trial (Management of OsteoArthritis) aims to test the effectiveness of two physiotherapy interventions for improving disability and pain in adults with hip or knee OA in New Zealand. Specifically, our primary objectives are to investigate whether: 1. Exercise therapy versus no exercise therapy improves disability at 12 months; 2. Manual physiotherapy versus no manual therapy improves disability at 12 months; 3. Providing physiotherapy programmes in addition to usual care is more cost-effective than usual care alone in the management of osteoarthritis at 24 months. Methods This is a 2 × 2 factorial randomised controlled trial. We plan to recruit 224 participants with hip or knee OA. Eligible participants will be randomly allocated to receive either: (a) a supervised multi-modal exercise therapy programme; (b) an individualised manual therapy programme; (c) both exercise therapy and manual therapy; or, (d) no trial physiotherapy. All participants will continue to receive usual medical care. The outcome assessors, orthopaedic surgeons, general medical practitioners, and statistician will be blind to group allocation until the statistical analysis is completed. The trial is funded by Health Research Council of New Zealand Project Grants (Project numbers 07/199, 07/200). Discussion The MOA Trial will be the first to investigate the effectiveness and cost-effectiveness of providing physiotherapy programmes of this kind, for the management of pain and disability in adults with hip or knee OA. Trial registration Australian New Zealand Clinical Trials Registry ref: ACTRN12608000130369.